Implementasi Algoritma Backtracking Pada Permainan Sudoku - Rahman, Fauzan Azima; Anubhakti, Dian (MEANS (Media Informasi Analisa dan Sistem), 2020)
Artificial intelligence is a field of computer science that is learning about computer devices that can be in the program using the machine in order to do commands from a programmer using certain instructions. One form of Artificial intelligence representation is a game or game. With the science of artificial intelligence then certain games will be able to be easily solved using computer assistance. One form of the game that can be inserted in an artificial intelligence game is Sudoku. The game is a form of numeric play where players are required to fill a blank box that is already available using a random number of numbers starting from 1 to 9. Many players are unable to complete this Sudoku game. This research uses Backtracking algorithms in solving sudoku puzzles. Research results in the form of applications capable of completing Sudoku puzzles